Increased Suitability of Poleward Climate for a Tropical Butterfly (Euripus nyctelius) (Lepidoptera: Nymphalidae) Accompanies its Successful Range Expansion. Issue 6 (8th November 2019) - Au, Tsun Fung; Bonebrake, Timothy C
Abstract: Distribution shifts are a common response in butterflies to a warming climate. Hong Kong has documented records of several new butterfly species in recent decades, comprising a high proportion of tropical species, some of which have successfully established. In this study, we examined possible drivers for the establishment of Euripus nyctelius Doubleday (Lepidoptera: Nymphalidae) by studying its thermal physiology and modeling current climate and future distributions projected by species distribution modeling (SDM). We found that E. nyctelius adults have a significantly higher critical thermal minimum than its local temperate relative, Hestina assimilis Linnaeus (Lepidoptera: Nymphalidae), suggesting a possible physiological constraint that may have been lifted with recent warming. SDMs provide further evidence that a shifting climate envelope may have improved the climate suitability for E. nyctelius in Hong Kong and South China—however, we cannot rule out the role of other drivers potentially influencing or driving range expansion, habitat change in particular. Conclusive attribution of warming-driven impacts for most tropical species is difficult or not possible due to a lack of historical or long-term data. Tropical insects will require a significant advancement in efforts to monitor species and populations across countries if we are to conclusively document climate-driven shifts in species distributions and manage the consequences of such species redistribution. Nevertheless, the warming climate and subsequent increased climatic suitability for tropical species in poleward areas, as shown here, is likely to result in future species redistribution events in subtropical and temperate ecosystems.